Chemotherapy with or without estramustine for treatment of castration-resistant prostate cancer: A systematic review and meta-analysis. Issue 39 (September 2016) - Qin, Zhiqiang; Li, Xiao; Zhang, Jianzhong; Tang, Jingyuan; Han, Peng; Xu, Zhen; Yu, Yajie; Yang, Chengdi; Wang, Chengming; Xu, Ting; Xu, Zicheng; Zou, Qing
Abstract: Background: Recently, increasing relevant studies researched the efficacy of castration resistant prostate cancer (CRPC) patients using chemotherapy with or without estramustine, in order to assess the efficacy and toxicity of combining estramustine with chemotherapy for the treatment of CRPC. Methods: Relevant randomized clinical trials were systematically searched from the databases Pubmed, Embase, and Web of science up to April 1, 2016. Data were centrally extracted and analyzed from the previous studies by 2 independent reviewers. The primary endpoint was overall survival (OS) with pooled hazard ratios. Secondary endpoints were prostate-specific antigen (PSA) response and grade 3 or 4 toxicity using pooled odds ratios. Stata version 12.0 software was used for statistical analysis. Results: Overall, this meta-analysis identified 9 eligible articles, including a total of 956 patients, who had been accrued between January 1, 1993 and December 1, 2010 and randomly divided into chemotherapy with estramustine and without estramustine. Chemotherapy (with or without estramustine) consisted of docetaxel, paclitaxel, ixabepilone, epirubicin, and vinblastine. Patients who received chemotherapy with estramustine had a better improvement in PSA response rate, comparing those without estramustine (OR = 1.84, 95% CI = 1.20–2.80). However, OS between the 2 groups indicated no significant differences (HR = 0.90, 95% CI = 0.77–1.05). Besides, these results of meta-analysis showed no obvious differences between these 2 groups in grade 3 or 4 adverse effects, including anemia (OR = 0.78, 95% CI = 0.38–1.57), neutropenia (OR = 0.91, 95% CI = 0.59–1.43), thrombocytopenia (OR = 0.68, 95% CI = 0.19–2.42), nausea (OR = 2.34, 95% CI = 0.81–6.72), vomiting (OR = 2.43, 95% CI = 0.69–8.51), diarrhea (OR = 3.45, 95% CI = 0.93–12.76), fatigue (OR = 0.67, 95% CI = 0.32–1.41), neuropathy (OR = 0.54, 95% CI = 0.21–1.44), allergic reaction (OR = 1.60, 95% CI = 0.37–6.84), thromboembolic event (OR = 2.18, 95% CI = 0.86–5.51), and edema (OR = 1.02, 95% CI = 0.18–5.95). Conclusions: This meta-analysis indicated chemotherapy with additional estramustine increased the PSA response rate. However, OS and grade 3 or 4 toxicity were not improved for these patients with CRPC.